Antioxidant capacity and major phenol compounds of horticultural plant materials not usually used. (November 2017) - Burri, Stina C.M.; Ekholm, Anders; Håkansson, Åsa; Tornberg, Eva; Rumpunen, Kimmo
Highlights: Antioxidant properties and phenols in plant materials not usually used were studied. Folin-Ciocalteu, FRAP and ABTS measures correlate with different phenol compounds. Large differences in antioxidant properties were found between and within species. Sea buckthorn and black currant leaves had the highest antioxidant capacity. Abstract: Horticultural plant materials not usually used from onion, carrot, beetroot, sea buckthorn, black and red currants as well as a wastewater powder from olive oil production were analyzed for total phenols content (FC), ferric reducing ability of plasma (FRAP), radical scavenging capacity (ABTS), and for major phenolic compounds by HPLC-MS. Antioxidant capacity and phenol content varied significantly between species and cultivars, with extracts of sea buckthorn leaves being superior. In different species, different phenolic compounds were closely associated with FRAP, ABTS and FC. For instance, hydrolysable tannins were major antioxidants in sea buckthorn whereas quercetin was the major antioxidant in onion peel and skin. This study shows that horticultural plant materials usually left in the field or waste materials from processing may have high antioxidant properties, and that extracts of these materials therefore could be of potential interest for development of antioxidant food additives.